Organización contable en la empresa diservet de la ciudad de Loja. Periodo del 01 de abril al 30 de junio del 2022. - Montaño Lozano, Yadira Verónica (2022)
The present research titled ACCOUNTING ORGANIZATION IN THE COMPANY "DISERVET" OF THE CITY OF LOJA, during April 1 to June 30, 2022", was developed with the purpose of having an adequate accounting organization that contributes to the company. It is worth mentioning that it is vital to inform the owner of the company about the financial situation and also the expected results. This research work is done in order to fulfilling one of the requirements prior to obtain the degree of Engineer in Accounting and Auditing. To accomplish the main objectives, an analysis of the line of business and nature of the business was made, which facilitated the preparation of a plan and manual of accounts according to the needs and requirements of the company, with their respective codification and description that can be used and serve as a guide for the accountant. Moreover, the initial inventory was prepared through the physical verification of values, assets, rights and obligations that the company has determining an asset of $ 586. 716.17, liabilities of $ 35,611.35 and equity of $ 551. 104.82 for the development of its economic activities, which allowed the elaboration of the initial situation statement as a starting point for the respective execution of the accounting process in the company, for the subsequent journalization in the respective daily book according to a chronological and systematic order from April 1 to June 30, 2022, through the inventory control system by multiple account which is used for academic purposes, thus continuing with the accounting process until the elaboration and presentation of the financial statements for the accounting period. Obtaining the economic and financial results as a conclusion since June 30, 2022; the statement of financial position with total assets of $ 642.795,41, liabilities of $ 85.700,39 and equity of $ 557.095,02. The Statement of Income reflects a net profit of $ 10.224,62 values that constitute a contribution and guide for the owner with the purpose of contributing to the development and improvement of the company.